DEVELOPMENT AND VALIDATION OF UV SPECTROSCOPIC METHOD FOR ESTIMATION OF LAMIVUDINE IN TABLET DOSAGE FORM - Sonar, Kalpesh V.; Sapkale, Prabodh; Jadhav, Anil; Deshmukh, Tushar; Patil, Swapnil; Murkute, Pallavi (International Journal of Current Pharmaceutical Research, 2017)
Objective: To develop and validate simple, rapid, linear, accurate, precise and economical UV Spectroscopic method for estimation of Lamivudine in tablet dosage form. Methods: The drug is freely soluble in analytical grade water. The drug was identified in terms of solubility studies and on the basis of melting point done on melting point apparatus of Equiptronics. It showed absorption maxima were determined in analytical grade water. The drug obeyed the Beer's law and showed a good correlation of concentration with absorption which reflects in linearity. The UV spectroscopic method was developed for estimation of lamivudine in tablet dosage form and also validated as per ICH guidelines. Results: The drug is freely soluble in analytical grade water, slightly soluble in methanol and practically insoluble in acetone. So, the analytical grade water is used as a diluent in the method. The melting point of lamivudine was found to be 160-161ËšC (uncorrected). It showed absorption maxima 268 nm in analytical grade water. On the basis of the absorption spectrum, the working concentration was set on 10Âµg/ml (PPM). The linearity was observed between 6-14 Î¼g/ml (PPM). The results of the analysis were validated by recovery studies. The recovery was found to be 98.7, 101 and 99.2% for three levels respectively. The % RSD for precision was found to be 0.62%. Conclusion: A simple, rapid, linear, accurate, precise and economical UV Spectroscopic method has been developed for estimation of Lamivudine in tablet dosage form. The method could be considered for the determination of Lamivudine in quality control laboratories.